A Study on Self–esteem and Academic Achievement of Undergraduates - , Souta Anjali, V. Vijaya Lakshmi, V. Kavitha Kiran (Archives of Current Research International, 2024)
Having high self-esteem is one of the most important things for any person, especially for the student. It helps them to perform better in academics and to be confident in their academics. This study aims to find the relationship between the self-esteem level and academic performance of undergraduate students. It was conducted on undergraduate students of Hyderabad. The sample size was 30 and the age group of the respondents was between 18-21 years. Exploratory research design was used in the study. Stratified random sampling method was used to collect the samples. Data was collected through interview method and further evaluated by frequency, percentage and correlation method. This study perceived that there is significant positive relationship between self-esteem level and academic performance of the undergraduates. The respondents who were having high self-esteem level were having good academic performance.